The Impact of Snake and Ladder Game the Second Grade Students' English Speaking Skill at SMAN 1 Kota Tidore - F. Mahmud, Adi; Khaerullah, Muhammad Saleh; HJ Wahid, Jusmin (FOSTER: Journal of English Language Teaching, 2023)
The study aims to obtain empirical data on the effectiveness of using the Snake and Ladder game in teaching English to second-grade students at SMAN 1 Kota Tidore. The study was conducted in experimental and control classes. There were 60 participants. The study was administered over three treatments. During the treatments, classes were taught English with the same content in different ways; the experimental class was taught using the Snake and Ladder game, while the control class was taught using the conventional method. The instrument used in this study was an oral test with a speaking rubric. The result stated that the post-test mean score of the experimental class was 80.43, while the post-test mean score of the control class was 70.73. The result of statistical hypothesis testing by using an independent sample t-test found that at the degree of significance of 5% (α = 0.05), the t-value was 2.247 while the t-table was 2.001, or t-value > t-table. Therefore, H0 was rejected and Ha was accepted. Furthermore, Cohen's formulation was used for the effect size of the Snake and Ladder, and the result was 0.24. Therefore, it is concluded that teaching English using the Snake and Ladder game is effective in teaching English.